(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
The study investigated innovative ethical decision-making for effective administration of Rivers State owned Universities. Three research objectives, three research questions and three hypotheses guided the study. The study adopted descriptive survey research design. The population and sample size of the study was 179 management staff comprising of 10 Principal Officers, 23 Dean of Faculties and 146 Head of Departments from Rivers State University and Ignatius Ajuru University of Education. The census sampling technique was used. The instrument used for data collection was a self-structured questionnaire titled “Innovative Ethical Decision-Making for Effective Administration Questionnaire” developed on a four-point rating scale of Very High Extent, High Extent, Low Extent and Very Low Extent. The instrument was validated by two experts in Measurement and Evaluation and Department of Educational Management in Rivers State University and tested for reliability using Cronbach Alpha method which yielded reliability indexes of 0.84, 0.80 and 0.82. Mean and standard deviation were used to answer the research questions while one-way ANOVA analysis was used to test the hypotheses at 0.05 significance level. The study found that innovative ethical decision-making such as technology integration, stakeholders’ inclusiveness and leadership to a high extent enhance effective administration of Rivers State owned Universities. Based on the findings, the study recommended among others that university management should adopt a proactive approach to integrating technology-driven administration by leveraging digital tools for academic planning, administrative communication, financial management and student services.